Towards a unitary conception of polycystic ovary syndrome - Rodríguez, Washington (2015)
The polycystic ovary syndrome (PCOS) and now called, was described by Stein and Leventhal and almost three quarters of a century, with associated symptoms characterized by oligomenorrhea, obesity and hirsutism, associated with the presence of polycystic ovaries. Subsequently, the published work about recovery cycle and achieving pregnancy after wedge resection of the ovaries in women with this disease, began to assume the possibility of a primarily ovarian defect, which caused were considered "disease polycystic ovary ".